2019
DOI: 10.3390/mi10120841
|View full text |Cite
|
Sign up to set email alerts
|

A Potential Application of Triangular Microwells to Entrap Single Cancer Cells: A Canine Cutaneous Mast Cell Tumor Model

Abstract: Cellular heterogeneity is a major hindrance, leading to the misunderstanding of dynamic cell biology. However, single cell analysis (SCA) has been used as a practical means to overcome this drawback. Many contemporary methodologies are available for single cell analysis; among these, microfluidics is the most attractive and effective technology, due to its advantages of low-volume specimen consumption, label-free evaluation, and real-time monitoring, among others. In this paper, a conceptual application for mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Polydimethylsiloxane (PDMS) was used for fabricating the microfluidic device, Exo-Load, by the soft UV lithography technique as described previously. 33 In brief, the photomask was first created, and the prototyping process was based on the standard process of silicon soft lithography with slight modifications, 34,35 such as adding several tweaks to the process. The photomask created over the printed circuit board (PCB) by Kinston was exposed to UV irradiation for 3 minutes.…”
Section: Fabrication Of the Exo-load Microfluidic Devicementioning
confidence: 99%
“…Polydimethylsiloxane (PDMS) was used for fabricating the microfluidic device, Exo-Load, by the soft UV lithography technique as described previously. 33 In brief, the photomask was first created, and the prototyping process was based on the standard process of silicon soft lithography with slight modifications, 34,35 such as adding several tweaks to the process. The photomask created over the printed circuit board (PCB) by Kinston was exposed to UV irradiation for 3 minutes.…”
Section: Fabrication Of the Exo-load Microfluidic Devicementioning
confidence: 99%
“…In veterinary science, there are a few reports on Oct-4 expression in putative CSCs in many cancers such as mast cell tumor, canine hepatocellular carcinomas, seminomas and thyroid carcinoma by immunohistochemistry (Webster et al, 2007b;Vargas et al, 2015) . In addition, the previous study and our preliminary study, demonstrated the Oct-4 expression at protein and mRNA levels by Immunohistochemistry and PCR technique, respectively (Eksiritrirat et al, 2012;Ketpun et al, 2013;Sailasuta et al, 2013). Hence, we believe that Oct-4 expressing cells might involve in the pathogenesis of MCT and MCT might have the stemness property.…”
Section: List Of Tablesmentioning
confidence: 54%
“…In many studies revealed that genetic alterations introduced the risk of tumors. Especially, c-Kit mutations at exon11 (the juxtamembrane domain; cytoplasmic kinase domain) can be activated proliferation in the absence of growth factors leading to unlimited hyperproliferation of the cells (Ketpun et al, 2013;Sailasuta et al, 2014).…”
Section: Pathogenesismentioning
confidence: 99%
“…In this study, the microfabrication of the devices had been accomplished under the standard photoresist-soft-lithography previously described in size-based polystyrene microsphere separations (Ketpun et al, 2015). And the replicas were constructed using polydimethylsiloxane (PDMS).…”
Section: The Architectures Of the Microfluidic Devices And Fabricationsmentioning
confidence: 99%